Direct oral anticoagulants for venous thromboembolism treatment and prophylaxis. Issue 8 (August 2016) - Yorkgitis, Brian K.
Abstract : ABSTRACT: Direct oral anticoagulants are a popular option for prevention and treatment of venous thromboembolism. However, they possess significantly different pharmacologic properties from warfarin. This article reviews approved direct oral anticoagulants, their indications, pharmacologic properties, monitoring, and reversal strategies.